Optimal Factor Income Taxation in the Presence of Unemployment - Erkki Koskela; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2000)
According to conventional wisdom internationally mobile capital should not be taxed or should be taxed at a lower rate than labour. An important underlying assumption behind this view is that there are no market imperfections, in particular that labour markets clear competitively. At least for Europe, which has been suffering from high unemployment f or a long time, this assumption does not seem appropriate. This paper studies the optimal factor taxation in the presence of unemployment which results from the union-firm wage bargaining both with optimal and restricted profit taxation when capital is internationally mobile and labour immobile. In setting tax rates the government is assumed to behave as a Stackelberg leader towards the private sector playing a Nash game. The main conclusion is that in the presence of unemployment, the conventional wisdom turns on its head; capital should generally be taxed at a higher rate than labour.
Keywords: 330; Optimal factor taxes; union wage bargaining; Stackelberg and Nash games